إعادة مقاربة الظاهرة القرآنيّة عند مالك بن نبي قراءة في الأسس النقديّة والآفاق الحضاريّة - عبدو, سارة (جامعة الوادي - University of Eloued, 2022)
ملخص: تهدف هذه الدراسة إلى الوقوف عند محاولة مالك بن نبي لتجديد مقاربة الظاهرة القرآنيّة باعتباره مشروعًا افتتاحيًّا تمخّض عنه بقيّة مشاريعه حول "النهضة"، ومهادًا صاغ من خلاله رؤاه وتصوّراته حولها، وسنسعى في مستوى أولّ لبيان موقف مالك بن نبي من مناهج المقاربات القديمة للقرآن وقضاياه سواءً الإسلاميّة أو الاستشراقية، ثمّ نحاول تدبّر المنطلقات والأسس العلميّة والنقديّة التي صاغها مالك بن نبي من أجل قراءة جديدة للظاهرة القرآنيّة، وفي الأخير سنخلص إلى جملة الآفاق والغايات التي يتوخّاها مالك بن نبي من خلال دعوته إلى تجديد منهج التعاطي مع القرآن ومساءلته. Abstract : This study aims to deal with Malek Bennabi’s attempt to renew the approach of the Qur’anic phenomenon as an introductory project that resulted from the rest of his projects on the “Renaissance,” and as a cradle through which he formulated his visions and perceptions about it. In the first place, we will seek to explain Malek Bennabi’s position on the ancient approaches to the Qur’an and its issues, whether Islamic or oriental. Then, we try to reflect on the scientific premises and foundations put forward by Malek Bennabi for a new reading of the Qur’anic phenomenon. Finally, we will conclude with a number of prospects and goals that Malek Bennabi seeks through his call for a renewal of the approach to dealing with the Qur’an and questioning it
مقال
Keywords: المقاربة ; الظاهرة القرآنية ; مالك بن نبي ; الأسس ; الآفاق